Brief commentary - Schattner, Mirta Ana (2002)
Recently, Tibbles et al. [1] reported that thrombopoietin (TPO) was capable of inducing P-selectin expression independently of calcium movements or platelet aggregation. They also found that leukocyte– platelet aggregates occurred after TPO cell stimulation most probably mediated by P-selection expression. Although they stated that they described a novel role for TPO in platelet function and platelet–leukocyte interactions both activities have been previously described by severalgroups [2–6]. Most of the studies showed that although TPO was not able to induce platelet activation alone it synergized platelet responses, including P-selectin expression, triggered by different agonists.